Unexpected reaction of antimony pentafluoride with a fluorinated propellane - Bremer, Matthias; Justus Liebig University Giessen (My University, 2024)
While 1,3-dehydro-5,7-difluoroadamantane 11 reacts with SbF5 in super acid media (SO2ClF) to generate the 1,3-dehydroadamant-5,7-diyl dication 1, 1,3-dehydro-5-fluoroadamantane 12 fails to react analogously to produce the 1,3-dehydroadamant-5-yl cation 9; instead, the 3,5-difluoro-1-adamantylcation 13 is formed. We present a computational study that explains this surprising behavior by the initial addition of Sb2F10 to the propellane bond present in 12. This is computed to be highly exothermic and leads to a zwitterionic (or ion-pair) species, which in turn reacts autocatalytically with HF to produce the observed fluorinated cation 13, SbF3, and SbF6–.
Keywords: ddc:540